Product videos “gone viral” - Lené Ehlers; Stephan van Schalkwyk (Communicare)
Viral video advertising is an avenue for marketers to spread information rapidly to a large, widespread audience. Video advertisements intended to “go viral” still get drowned out by media clutter. Content characteristics, positive affect and social motivations of the viewer have been highlighted as factors that influence the forwarding intention of viral product videos. This study investigated these factors and their impact on forwarding intention. The results from a realised sample of 250 respondents confirmed the relationship between content characteristics and forwarding intention, the mediating effect of social motivations, and the multiple mediating effect of positive affect and social motivations but not the mediating effect of positive affect alone. As a result, marketing managers should focus on both positive affect (evoked emotions of enthusiasm, pride, inspiration, and attentiveness) and social motivations (appealing to consumers’ need for distinctiveness, affiliation, and altruism) of the viewer when creating video advertisements intended for virality.